NARKOBA DAN PERSPEKTIF DAKWAH - Darizal Dahlan (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
Writer explains about drug andits danger, as Dakwah  concept in fighting against narkoba and as contemplation with presumably assist to improve awareness of people through dakwah activity.The discussion talks about: 1. congeniality of Narkoba2. Islamic law in seeing of produce and sell drug 3. Islamic law penalization in consumingdrug 4. Drug in dakwah perspective